Rethinking the Efficiency of the Common Law - Sokol, D. Daniel (2019)
This Article shows how Posner and other scholars who claimed that common law was efficient misunderstood the structure of common law. If common law was more efficient, there would have been a noticeable push across most, if not all, doctrines to greater efficiency. This has not been the case. Rather, common law, better recast as a “platform,” could, under a certain set of parameters, lead to efficient outcomes. Next, the Article’s analysis suggests that while not every judge thinks about efficiency in decisionmaking, there must be some architectural or governance feature pushing in the direction of efficiency—which exists in some areas of law and not in others. This Article explains two-sided markets, or platforms, generally and applies the modular open-source platform model to judge made law. In doing so, it explores concepts that impact the efficiency of such platforms—platform governance, modularity, and fragmentation. Then, this Article applies the understanding of platforms to several areas of law that might be understood as more prone to economic analysis because the issues addressed in law tend to be more “economic,” such as torts, bankruptcy, patents, and corporations. In these areas, no combination of platform architecture and modularity has allowed for the development of more efficient legal rules as a general matter. Finally, this Article studies antitrust law as the one area of law that suggests that the efficiency of common law is possible and the causal mechanism of necessary conditions that needs to be met. Antitrust law is different than other areas of law because of a singular goal, an architectural governance based on a single federal court (the Supreme Court) with few substantive legislative changes for the past one hundred years, which provides for coherent governance of the platform. This Article concludes by discussing the implications of an efficient platform design for other areas of law